Strategi Komunitas Club Motor Honda CB Dalam Masyarakat Surabaya - Iqbal, Ghalih Rafiano; Yenny, Yenny (Universitas Dr.Soetomo, 2021)
The automotive world in Indonesia is growing and getting more advanced. It can be seen from the many communities in the automotive sector, especially the motorcycle community. Motorcycle communities are increasingly popping up and growing in big cities to remote areas. In Surabaya there are many motorcycle communities, one of which is the Honda CB community. This community consists of Honda CB motorcycle owners in the Surabaya area. In this study, the author discusses the communication strategy of the Honda CB Community in the Surabaya community. Solidarity in this community includes internal solidarity and external solidarity. Internal solidarity includes social relationships that occur among members of the Honda CB community. External solidarity that includes social relations between members of Honda CB and the Honda CB community and the people of Surabaya. This research is a qualitative research with descriptive analysis. Descriptive analysis method was chosen with the aim of describing the phenomena that occur in accordance with the facts as they are. Sources of data in this study obtained from quotes, behavior, written sources, and photos. Data collection methods used in this study were observation, interviews, and documentation. Interviews based on sampling techniques conducted internally based on subjects who have the most representative information.